Bioanalytical Assay Development and Validation for the Pharmacokinetic Study of GMC1, a Novel FKBP52 Co-chaperone Inhibitor for Castration Resistant Prostate Cancer - Oscar Ekpenyong; Candace Cooper; Jing Ma; Naihsuan C. Guy; Ashley N. Payan; Fuqiang Ban; Artem Cherkasov; Marc B. Cox; Dong Liang; Huan Xie (MDPI AG, 2020)
Background: GMC1 (2-(1H-benzimidazol-2-ylsulfanyl)-N-[(Z)-(4-methoxyphenyl) methylideneamino] acetamide) effectively inhibits androgen receptor function by binding directly to FKBP52. This is a novel mechanism for the treatment of castration resistant prostate cancer (CRPC). Methods: an LC-MS/MS method was developed and validated to quantify GMC1 in plasma and urine from pharmacokinetics studies in rats. An ultra-high-performance liquid chromatography (UHPLC) system equipped with a Waters XTerra MS C18 column was used for chromatographic separation by gradient elution with 0.1% (v/v) formic acid in water and methanol. A Sciex 4000 QTRAP® mass spectrometer was used for analysis by multiple reaction monitoring (MRM) in positive mode; the specific ions [M+H]+m/z 340.995 → m/z 191.000 and [M+H]+ m/z 266.013 → m/z 234.000 were monitored for GMC1 and internal standard (albendazole), respectively. Results: GMC1 and albendazole had retention times of 1.68 and 1.66 min, respectively. The calibration curves for the determination of GMC1 in rat plasma and urine were linear from 1-1000 ng/mL. The LC-MS/MS method was validated with intra- and inter-day accuracy and precision within the 15% acceptance limit. The extraction recovery values of GMC1 from rat plasma and urine were greater than 95.0 ± 2.1% and 97.6 ± 4.6%, respectively, with no significant interfering matrix effect. GMC1 is stable under expected sample handling, storage, preparation and LC-MS/MS analysis conditions. Conclusions: Pharmacokinetic evaluation of GMC1 revealed that the molecule has a biexponential disposition in rats, is distributed rapidly and extensively, has a long elimination half-life, and appears to be eliminated primarily by first order kinetics.